1980
DOI: 10.1002/cne.901940110
|View full text |Cite
|
Sign up to set email alerts
|

Development and degeneration of retina in rds mutant mice: Light microscopy

Abstract: Changes during the development and degeneration of the retina in 020/A mice, which are homozygous for the newly reported rds (retinal degeneration slow), gene were studied by histological and enzyme-histochemical methods with Balb/c mice carrying the normal allele as control. During normal development the total thickness of the retina grows from the time of birth till the age of 21 days and thereafter gradually diminishes, while the thicknesses of the component layers show a characteristic and differential cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
106
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(116 citation statements)
references
References 42 publications
9
106
1
Order By: Relevance
“…Such patterns of hypopigmentation, due to a variety of causes including but not limited to RPE cell dropout, have been seen in fundus photographs of most of the known murine inherited retinal degenerations~Hawes et al, 1999;Chang et al, 2002;Mehalow et al, 2003;Pang et al, 2005!. As we have reported here, several studies correlate areas of RPE cell thinning with the apposing and localized loss of photoreceptor cell bodies comprising the ONL~Caley et al, 1972;Sanyal & Bal, 1973;Sanyal et al, 1980;LaVail et al, 1982LaVail et al, , 1993Blanks et al, 1982;Messer et al, 1993!. As in other photoreceptor degenerations, Müller cells fill in space left by these dying photoreceptors. Though immunocytochemistry shows that there is some upregulation of GFAP in these cells, as has been seen in other retinal degenerations~Eisenfeld et al, 1984;Lewis et al, 1994!, we , there is an increase in apoptotic profiles though they are still restricted to the inner retinal layers.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Such patterns of hypopigmentation, due to a variety of causes including but not limited to RPE cell dropout, have been seen in fundus photographs of most of the known murine inherited retinal degenerations~Hawes et al, 1999;Chang et al, 2002;Mehalow et al, 2003;Pang et al, 2005!. As we have reported here, several studies correlate areas of RPE cell thinning with the apposing and localized loss of photoreceptor cell bodies comprising the ONL~Caley et al, 1972;Sanyal & Bal, 1973;Sanyal et al, 1980;LaVail et al, 1982LaVail et al, , 1993Blanks et al, 1982;Messer et al, 1993!. As in other photoreceptor degenerations, Müller cells fill in space left by these dying photoreceptors. Though immunocytochemistry shows that there is some upregulation of GFAP in these cells, as has been seen in other retinal degenerations~Eisenfeld et al, 1984;Lewis et al, 1994!, we , there is an increase in apoptotic profiles though they are still restricted to the inner retinal layers.…”
Section: Discussionsupporting
confidence: 68%
“…data showed a strong correlation between the time course of photoreceptor loss in each strain and the gradual extinction of the a-wave in each~Chang et al, 1993a; Heckenlively et al, 1993b; Nusinowitz et al, 1997!. These results indicated that the time course of the rd-3 rod0cone degeneration is of intermediate duration when compared to other retinal degenerations in micẽ Carter-Dawson et al, 1978;Messer et al, 1993;Mullen & LaVail, 1975;Sanyal et al, 1980!. Photoreceptor degeneration begins at the time of outer segment differentiation, reaching completion in 2-4 months.…”
Section: Introductionmentioning
confidence: 96%
“…The RDS/PRPH2 gene codes for a photoreceptor-specific glycoprotein called retinal degeneration slow (RDS 2 or peripherin-2), which is a member of the tetraspanin family of proteins and is critical for the proper formation of both rod and cone photoreceptor outer segments (OSs) (1)(2)(3)(4)(5)(6)(7)(8). The OS is an organelle comprising a series of flattened opsin-packed discs and is specialized to detect incoming light and initiate phototransduction (9 -11).…”
mentioning
confidence: 99%
“…Over 80 individual mutations of the RDS/PRPH2 gene in humans have been associated with significant diseases of the retina that can range from the rod-dominant retinitis pigmentosa to the cone-dominant diseases cone-rod dystrophy and macular degeneration (12). Additionally, extensive studies in mouse models have clearly demonstrated the importance of the RDS protein to retinal structure and function (2,(13)(14)(15)(16)(17)(18). In mice heterozygous for the Rds gene (rds ϩ/Ϫ ), the OSs become highly disorganized, and the discs adopt a bizarre whorl-like morphology.…”
mentioning
confidence: 99%
“…At 72 hr after MNU treatment, detachment of the pigment epithelial cells from Bruch's membrane was seen, and, at day 7, 21 and 35, migrating pigment-containing cells were present in all layers of the retina. In agreement to inherited retinal degeneration mice [5,47], Müller cells, macrophages and migrated pigment epithelial cells are involved in removal of apoptotic cells. However, the migrated melanincontaining cells were not in contact with blood vessels.…”
Section: Time Course Of Mnu-induced Retinal Degeneration In Ratsmentioning
confidence: 92%